Metabolic reprogramming in lung cancer and its clinical implication - Huang, Qingqiu; Fan, Lisha; Gong, Mingjing; Ren, Juntong; Chen, Chen; Xie, Shenglong (Frontiers in Pharmacology, 2024)
Lung cancer has posed a significant challenge to global health, and related study has been a hot topic in oncology. This article focuses on metabolic reprogramming of lung cancer cells, a process to adapt to energy demands and biosynthetic needs, supporting the proliferation and development of tumor cells. In this study, the latest studies on lung cancer tumor metabolism were reviewed, including the impact of metabolic products and metabolic enzymes on the occurrence and development of lung cancer, as well as the progress in the field of lung cancer treatment targeting relevant metabolic pathways. This provides some promising potential directions into exploring lung cancer tumor metabolism and helps researchers to better understand lung cancer.